Fabrication of nanopillar arrays by combining electroforming and injection molding. Issue 5 (September 2016) - Jiang, Bing-yan; Zhou, Ming-yong; Weng, Can; Zhang, Lu; Lv, Hui
Abstract Injection molding is regarded as one of the cost-effective molding technologies to produce polymer items in large numbers. In this paper, a fabrication method for nanopillar arrays by combining electroforming and injection molding has been proposed. Mold inserts with satisfactory replication and high homogeneity have been electroformed by a self-designed micro-electroforming equipment. A variotherm injection molding technique with electrical heating and oil cooling has been realized for precise temperature control on mold cavity. It is shown that the mold cavity temperature can be represented by the measured temperature of the thermocouple installed in the mold. Nanopillars are found to be almost filled during the packing stage. Circular structures at the top of nanopillars have been observed under a lower packing pressure. As a key processing parameter, mold temperature is recommended as 25 °C higher than the polymer glass transition temperature. To ensure better replication quality of nano-patterns, the demolding temperature should be around 10 °C lower than the polymer glass transition temperature.